Strategies For Improving Student Learning: Examining Strategies for Enhanced Mathematics and Science Learning in Ambala District (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A shared aim, alignment ofcurriculum, instruction and assessment, and data-driven instruction are keys tohigh student achievement in mathematics and science in the  Ambala district. This paper willaddress structures and strategies one district used in improving studentachievement in mathematics and science learning, from the development of ashared aim and a systematic focus on curriculum, instruction, and assessment tointensive analysis of assessment data for making instructional decisions tomeet student learning needs